2022
DOI: 10.1111/aas.14102
|View full text |Cite
|
Sign up to set email alerts
|

Fraction of inspired oxygen during general anesthesia for non‐cardiac surgery: Systematic review and meta‐analysis

Abstract: Background: Controversy exists regarding the effects of a high versus a low intraoperative fraction of inspired oxygen (FiO 2 ) in adults undergoing general anesthesia. This systematic review and meta-analysis investigated the effect of a high versus a low FiO 2 on postoperative outcomes.Methods: PubMed and Embase were searched on March 22, 2022 for randomized clinical trials investigating the effect of different FiO 2 levels in adults undergoing general anesthesia for non-cardiac surgery. Two investigators in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 70 publications
1
12
2
Order By: Relevance
“…Given this, additional trials are needed before a definitive effect can be concluded. Moreover, it is important to consider these results in the context of other outcomes, such as mortality, length of stay, and postoperative complications as reported previously 4,6 …”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Given this, additional trials are needed before a definitive effect can be concluded. Moreover, it is important to consider these results in the context of other outcomes, such as mortality, length of stay, and postoperative complications as reported previously 4,6 …”
Section: Discussionmentioning
confidence: 85%
“…Overall, the search identified 23,454 unique records of which 535 full-text articles were assessed for eligibility. Of 209 manuscripts included in previous reviews, [4][5][6][7] 63 manuscripts including relevant outcomes for the current manuscript were identified. Review of references and previous reviews resulted in identification of two additional manuscripts, yielding a total of 65 manuscripts (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations